PENGARUH METODE KEDISIPLINAN TERHADAP PERILAKU BULLYINGPADA REMAJA - Apsari, Fitri (TALENTA, 2015)
The problems of violence in the school environment or education has showed a very alarming, 16% of the final grade students said that they had been threatened with a weapon at school, 7% said they had been injured with a weapon (Santrock, 2007). Handling bullyingbehavior requires a lot of time and supervision so that in some cases need to be addressed by means of a multidisciplinary (Balhaqi and Sugiarmin, 2008).Data analysis techniques are used to study the behavior of bullyingbased on gender by using Anova one lane while to figure out the dynamics between variables using multiple regression.Results of the data analysis states that: There was a significant relationship between self-esteem and school discipline with bullyingbehavior. Bullyingbehavior in adolescents in schools is dominated by male students than female. Male subjects involved bullyingbehavior as much as 30.30% and female subjects as much as 24.97%. The reason why boys tend to be more aggressive psychologically explained this is related to their need to demonstrate physical strength, but also biological factors must still be considered (Obrdalj and Rumboltd, 2008).Discipline functions can individually adjust socially at school became a regular, nothing behave and act their own way. the formation of high school discipline for students to take responsibility for any problems that exist, so that any student can judge for itself the extent to which students have the potential to excel with multidisciplinary applied. This will lessen the intensity of the bullyingbehavior.